Intimate partner violence and its association with mental health problems: The importance of childhood violence – The SAMINOR 2 Questionnaire Survey - Eriksen, Astrid; Melhus, Marita; Jacobsen, Bjarne K.; Schei, Berit; Broderstad, Ann-Ragnhild (Scandinavian Journal of Public Health, 2021)
Aims: This study aims to estimate the prevalence of intimate partner violence (IPV) and its association with psychological distress and symptoms of post-traumatic stress (PTS) among Sami and non-Sami and to explore whether the association between IPV and mental health is modified by exposure to childhood violence (CV). These issues are scarcely studied among the Sami. Methods: This study was based on the cross-sectional SAMINOR 2 Questionnaire Survey, a part of the Population-based Study on Health and Living Conditions in Regions with Sami and Norwegian Populations (SAMINOR). Chi-square tests and two-sample t-tests were used to test differences between groups. Multiple linear regression analysis was applied to explore the association between IPV/CV and continuous scores of psychological distress and symptoms of post-traumatic stress. Results: Experiences of IPV (emotional, physical, and/or sexual) were reported by 12.8% of women and 2.0% of men. A significantly higher proportion of Sami women reported exposure to emotional (12.4 v. 9.5%, p = 0.003), physical (11.6 v. 6.9%, p < 0.001), and any IPV (17.2 v. 11.8%, p < 0.001) compared to non-Sami women. There were no ethnic differences in sexual IPV among women (2%). Exposure to IPV was associated with a higher score of psychological distress and PTS and was highest among those exposed to both IPV and CV. Conclusions: Sami women reported the highest prevalence of IPV. The association between IPV/CV and mental health problems did not differ by ethnicity or gender. The most severe mental health problems were observed for those who were exposed to both IPV and CV.